The cognitive and neural correlates of written language: a selective review of bilingualism. Issue 1 (2nd January 2021) - Waldie, Karen E.; Badzakova-Trajkov, Gjurgjica; Park, Haeme R. P.; Zheng, Yuxuan; Neumann, Denise; Zamani Foroushani, Nasrin
ABSTRACT: Approximately half the world's population can speak more than one language. In this selective review, we consider whether there is an advantage to bilingualism and whether the bilingual brain is different in terms of both executive functioning and lexical decision-making. We focus on two functional MRI studies from our lab where task performance and brain activation from late proficient bilinguals when using their first (L1) and second (L2) language are compared to matched monolinguals. In Study One, monolinguals produced greater activation than bilinguals during Stroop performance, regardless of task demands. During interference, monolinguals showed more posterior brain activation relative to bilinguals and during response conﬂict, monolinguals showed greater activation in the anterior cingulate and prefrontal regions. In Study Two, bilinguals recruited more extensive networks when processing L2 than L1 and when compared to monolinguals. Bilinguals also showed weaker lateralisation, particularly in the temporal lobe, during both L1 and L2 lexical decisions. Taken together, learning a second language late confers a benefit to executive functioning but at the expense of decreased cortical efficiency. Research is now required to determine the extent of plasticity in both language- and non-language dedicated areas, and how this plasticity is modulated by experience throughout the lifespan.